(3GdGSJQGJjLjGJ GdMOjKI dEOGQI GdGReGJ aj Xd YGde eJZjQ (B/s - (3LdOI, Sdje HWQSs ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2007)
(3eaGgje CSGSjI aj EOGQI GdCReGJ , GdeOGNd GdeNJdaI dOQGSI GdGReGJ h aQjb EOGQI GdCReGJ , ahGFO GdGReI h GSJQGJjLjGJ ehGLgI GdCReGJ , GdbQGQ h OhQg aj ZOGQI GdGReGJ , VZhW GdYed , GdJaGhV h EOGQI GdGReGJ , GdYdGbGJ GdYGeI h GOGQI GdGReGJ , EOGQI GdGReGJ aj GdeOGQS h GdLGeYGJ , EOGQI GdHjFI h EOGQI GdGReGJ , EOGQI GdCReGJ aj HhQUGJ GdChQGb GdeGdjI , JWHjb h EOGQI GdCReGJ aj eLGd GdYedjGJ GdGdcJQhfjI (B.s
(3eQGLY U(B.217s
Keywords: (3EOGQI(B- (3CReGJs; (3GdEOGQI GdYGeIs; (3GdCReGJs